Produção integrada de etanol de cana-de-açúcar e milho em usinas flex: simulação e análises tecno-econômica e ambiental - Oliveira, Luiza Stolte Bezerra Lisbôa de (2022)
Liquid biofuels are important alternatives to traditional fossil fuels, not only environmentally, but also socially and from an energy security standpoint. Brazil has a consolidated infrastructure for the production, distribution, and commercialization of biofuels, in particular ethanol. Even though sugarcane has been the main raw material used for ethanol production for years, the processing of corn for ethanol production has been experiencing a rapid growth, especially in the Center-West region. This project evaluated the technical, economic and environmental feasibility of corn ethanol production integrated to a standalone sugarcane ethanol distillery (called flex plant). The standalone distillery processes 4 million tons of sugarcane in the harvest season, and one scenario considers cogeneration from sugarcane straw during the off-season. Two scenarios for corn ethanol production were studied: conventional (sequential liquefaction, saccharification and fermentation) and simultaneous (simultaneous saccharification and fermentation of non-liquefied starch), each processing about 246 and 208 thousand tons of corn in the off-season. The process simulator Aspen Plus was used to estimate capital costs and process yields. The incremental capital cost for the flex plants was 53,8 and 52,9 million dollars for the conventional and simultaneous scenarios, respectively, and the increase in anhydrous ethanol production, relative to the amount produced in the harvest season from sugarcane, was 25,2 and 21,3%. The NPV (Net Present Value) of the flex plants was 86,1 and 63,9 million dollars, following an incremental approach. However, the Maximum Purchase Price for Corn (MPPC) was around 58 R$/60kg, which is lower than the price in Mato Grosso for February 2022 (75 R$/60kg). The risk analysis indicated that the probability of profitability for the incremental flex plants is around 68%. The open software OpenLCA was used to perform the Life Cycle Assessment (LCA). The incorporation of corn ethanol production increased the impact in the global warming category by 6% (from 0,533 to 0,564 kg CO2 eq/kg ethanol), relative to the value obtained for the standalone distillery with cogeneration from straw. In addition, the impact on the freshwater ecotoxicity category was 6 to 7 times greater for the flex scenarios than for the standalone distillery, due to the high application of pesticides during corn cultivation. This suggests that improvements to this impact category should be made at the agricultural level.